PRIHATIN DENGAN TEKS BACAAN BAHASA INGGRIS “UJI COBA UJIAN NASIONAL II 2013/2014 SEKOLAH MENENGAH ATAS, KOTA SEMARANG”: SEKEDAR ULASAN AKADEMIS - Sarah Sumponogati (Universitas Stikubank (UNISBANK) Semarang, 2014)
This article reviews two texts used in ‘National Examination Try-out II of 2013/2014 Senior High Schools’ since to the best of the writers’ knowledge the two texts do not represent good texts for a language test. In this respect, the writer shall review the test based on grammaticality, coherence and cohesion of the texts under study. However, it should be noted that this article does not necessarily mean that the writer would discredit the test writer since several factors, such as hectic time, low payment, overloaded teaching tasks, may influence the validity and reliability of the test being produced. Recommended in this article include: (1) the use of authentic texts taken from English newspaper or cyber resources, (2) proofreading prior to publication. Key words: text, exam, grammaticality, coherence